انعكاسات جائحة كورونا على التكوين في معهد التربية البدنية والرياضية - سقيل, فريال (Institut d’Éducation Physique et Sportive mostaganem 2021/2022, 2021)
هدفت الدارسة إلى تقويم الكفاءات التدريسية لأساتذة التربية البدنية و الرياضة فيالمرحلة المتوسطة في ظل الجيل الثاني من الإصلاحات التربوية وذلك من خلالتحديد أهم الكفاءات التدريسية اللازمة الواجب توافرها لدى أساتذة التربية البدنية الرياضية وفي الأخير الوقوف على مدى قدرة أستاذ التربية البدنية و الرياضة على توظيف تلك الكفاءات داخل الحصة ،هذا وقد استخدم فريق البحث المنهج الوصفيبأسلوب المسحي لملائمته لمشكلة الدارسة،وشملت عينة الدارسة 50 أستاذ للتربية البدنية و الرياضة للطور المتوسط و الثانوي بولاية غليزان وتم اختيارهم بطريقة عشوائية وقمنا باستعمال استمارة استبيانيه للكفاءات التدريسية كأداة لجمعالبيانات واستعملنا برنامج الحزم الإحصائيةSpssكأداة إحصائية. وتوصلت إلى مستو ى كل من الكفاءات التدريسية )التخطيطية، التنفيذية، التقويمية، المهنية(لأساتذة التربية البدنية في مرحلة التعليم المتوسط في ظل الجيل الثاني من الإصلاحات التربوية مرتفعة. The study aimed to evaluating the teaching competencies of teachers of physical education and sports in the middle stage in light of the second generation of educational reforms by identifying the most important teaching competencies needed to be available to teachers of physical education and sports, and in the end to determine the extent of the ability of the professor of physical education and sports On employing these competencies within the class, the research team used the descriptive approach to suit the problem of the study, and the study sample included 40 teachers of physical education and sports for the intermediate stage, and they were randomly selected,We used a questionnaire for the teaching competencies as a tool to collect data, and we used the statistical packages program Spss as a statistical tool. And we reached the level of each of the teaching competencies (planning, executive, evaluation, and professional) of physical education and sports teachers in the intermediate education stage in light of the second generation of educational reforms is high.
LEPS-2022-7
Keywords: الكفاءة التدريسية - أستاذ التربية البدنية والرياضية - الوسط المدرسي - الجيل الثاني. / evaluation - teaching competencies - physical education and sports teachers - intermediate education - second generation